(untitled) (Bioscience Journal, 2015)
Yacon is a tuberous root that has functional components in its composition, such as fructooligosaccharides (FOS). The objective of this study was to evaluate physicochemical and sensory characteristics of diet and conventional cakes made with yacon in natura and its respective flour. Cakes were prepared in chocolate and carrot flavors with the addition of 50% yacon in natura and 70% yacon flour. Cakes prepared with 50% yacon in natura with the addition of sucrose in the formula showed physical aspects closer to conventional cakes. The yield of the cakes was considered satisfactory at around 90%, regardless of yacon in natura or yacon flour usage. The chocolate cakes had higher ratings regarding the sensory attributes and the purchase intent in relation to the carrot cakes, especially when using yacon in natura in the formula. The cakes containing sweetener were rated as good as those with sucrose, especially in regards to the flavor of the chocolate cakes. According to the chemical composition, cakes with 70% yacon flour had higher dietary fiber content as well as FOS and are considered foods with high fiber content, giving credit to their claim as a functional food.